Let's prevent diabetes: study protocol for a cluster randomised controlled trial of an educational intervention in a multi-ethnic UK population with screen detected impaired glucose regulation. - Gray, L; Khunti, K; Williams, S; Goldby, S; Troughton, J; Yates, T; Gray, A; Davies, M (2012)
BACKGROUND: The prevention of type 2 diabetes is a globally recognised health care priority, but there is a lack of rigorous research investigating optimal methods of translating diabetes prevention programmes, based on the promotion of a healthy lifestyle, into routine primary care. The aim of the study is to establish whether a pragmatic structured education programme targeting lifestyle and behaviour change in conjunction with motivational maintenance via the telephone can reduce the incidence of type 2 diabetes in people with impaired glucose regulation (a composite of impaired glucose tolerance and/or impaired fasting glucose) identified through a validated risk score screening programme in primary care. DESIGN: Cluster randomised controlled trial undertaken at the level of primary care practices. Follow-up will be conducted at 12, 24 and 36 months. The primary outcome is the incidence of type 2 diabetes. Secondary outcomes include changes in HbA1c, blood glucose levels, cardiovascular risk, the presence of the Metabolic Syndrome and the cost-effectiveness of the intervention. METHODS: The study consists of screening and intervention phases within 44 general practices coordinated from a single academic research centre. Those at high risk of impaired glucose regulation or type 2 diabetes are identified using a risk score and invited for screening using a 75 g-oral glucose tolerance test. Those with screen detected impaired glucose regulation will be invited to take part in the trial. Practices will be randomised to standard care or the intensive arm. Participants from intensive arm practices will receive a structured education programme with motivational maintenance via the telephone and annual refresher sessions. The study will run from 2009-2014. DISCUSSION: This study will provide new evidence surrounding the long-term effectiveness of a diabetes prevention programme conducted within routine primary care in the United Kingdom. TRIAL REGISTRATION: Clinicaltrials.gov NCT00677937.